Estimation of biomass and animal load in riverside wetlands using multispecitral orthophotographs acquired with microsensors transporated in unmanned aerial vehicles “Drone” - Puelles Condori, Blanca Nélida (2022)
The study was carried out in the river wetlands of San Pedro and San Pablo adjacent to the Vilcanota River in the province of Canchis, Cusco, in southern Peru. The objective was to estimate the production of aerial biomass and the animal carrying capacity of these wetlands from the analysis of samples acquired in the field and NDVI orthophotographs. The images were acquired with a Parrot sequoia multispectral camera, transported by a Matrice 100dji Drone and processed in Pix4D and ArcGIS 10.6 software. The study identified 5 types of land use: wetland, agriculture, urbanization, salt and water. The estimated biomass production with field data was 2,359.46 kg/ha and 2,885.78 kg/ha, while the estimate with NDVI orthophotographs was 2,321.71 kg/ha and 3,048.72 Kg/ha for the wetlands of San Pablo and San Pedro respectively. The estimated animal load capacity from field data was 0.48 U.V/ha/year and 4.79 U.O/ha/year in the San Pablo wetland and 0.59 U.V/ha/year and 5.86 U.O/ha/year in the San Pedro wetland, the same variable estimated from NDVI orthophotographs for the San Pablo wetland was 0.47 U.V/Ha/year and 4.71 U.O/ha/year and for the San Pedro wetland 0.62 U.V/ha/ha/year and 6.19 U.O/ha/year of animal load was obtained. Estimates made for carrying capacity show differences of 1.87% for cattle, 2.13% for sheep.